Intimate with Walt : selections from Whitman's conversations with Horace Traubel, 1888-1892 - Traubel, Horace, 1858-1919 (Iowa Whitman series., 2001)
In March 1888 Horace Traubel, Whitman's loyal and hardworking assistant, began to record his almost daily conversations with the most famous resident of Camden. The result: more than 1,900,000 words that were eventually published between 1906 and 1996 in nine volumes. Titled With Walt Whitman in Camden, these volumes contain much that is mundane and repetitive, but they also include many passages crucial for a full and humane understanding of America's first great national poet.